PROGRESS TOWARDS MEASLES ELIMINATION IN MOROCCO - Benamar, Touria; Alla, Amal; Cherkaoui, Imad; Tajounte, Latifa; Laskri, Ahmed; Ziani, Moncef; Filali-Maltouf, Abdelkarim; El Aouad, Rajae (European Scientific Journal, ESJ, 2014)
In order to eliminate measles in Morocco, a mass vaccination campaign targeting children aged from 9 months to14 years was conducted on May-June 2008. The vaccination coverage was estimated to be 99%. This study aims to assess the impact of the measles mass vaccination campaign on measles incidence based on sensitive surveillance system. For this purpose, a laboratory case-based surveillance was set up during 2010. Epidemiological definition of suspected measles cases was fixed. Specimens were collected through all primary health centers and hospitals at national level and suspected cases were confirmed by serological tests. Measles strains isolated during outbreaks were genotyped. The performance of the surveillance system was evaluated according to the World Health Organization indicators. The incidence was calculated based on the epidemiological surveillance data, and compared to the World Health Organization incidence, which is 1 case per million per year. 1214 suspected cases were notified and 1083 measles samples were analyzed and 45 % (491/1083) were serologically confirmed and 115 cases were confirmed by epidemiological linkage. Molecular epidemiology shows that genotype D4 is endemic since 2008. The WHO indicators show that the sensitivity of surveillance system is low. Despite this weak sensitivity, epidemiological data show that measles incidence is higher than that recommended by WHO, and reached 19.18/1 000 000. In conclusions, Measles mass campaign did not reach the goal expected. A second mass campaign should be planned in the near future to eliminate the disease in the country.